Effects of personality on the association between paroxetine plasma concentration and response - Tomita T (Dove Medical Press, 2018)
Tetsu Tomita,1 Norio Yasui-Furukori,1 Taku Nakagami,2 Shoko Tsuchimine,3 Masamichi Ishioka,4 Ayako Kaneda,1 Kazuhiko Nakamura1 1Department of Neuropsychiatry, Graduate School of Medicine, Hirosaki University, Hirosaki, Japan; 2Department of Psychiatry, Nakagami Mental Clinic, Odate, Japan; 3Department of Mental Disorder Research, National Institute of Neuroscience, National Center of Neurology and Psychiatry, Tokyo, Japan; 4Department of Psychiatry, Minato Hospital, Hachinohe, Japan Background: We studied the differences between groups that were divided according to personality characteristics with respect to the relationship between drug concentration and symptom improvement.Methods: A total of 120 patients with major depressive disorder were treated with paroxetine for 6 weeks, and 89 patients completed the protocol. The Montgomery–Åsberg Depression Rating Scale (MADRS) was used to evaluate the patients. Patients’ paroxetine plasma concentrations at week 6 were measured. Their personalities were evaluated by the Temperament and Character Inventory (TCI) at the first visit. We divided the patients into two groups according to the median of each TCI dimension. We compared the responder rate between “high” and “low” groups in each TCI dimension and analyzed Pearson’s correlation coefficients of paroxetine plasma concentration and MADRS-improvement rate.Results: A total of 62 patients completed the TCI. Low-novelty-seeking, high-harm-avoidance, low-reward-dependence, and low-self-directedness groups exhibited significant negative correlations between paroxetine plasma concentration and MADRS improvement. Among the groups with combined personality traits, the high-harm-avoidance and low-self-directedness groups showed a markedly significant negative correlation.Conclusion: Patients with depression exhibiting specific personality traits, especially those with high harm-avoidance and low self-directedness scores, exhibited a significant negative association between paroxetine plasma concentration and MADRS-improvement rate. Therefore, a lower dose might be suitable for patients with specific personality traits. Keywords: depression, paroxetine, concentration, personality, Temperament and Character Inventory, TCI